(3GdZQjH GdeUfas - (3GdbGSe Hf SdGe GdgQhj GdCROj GdNRGYj, CHh YHjO, J (B224 (3g` s ((3GHh Ydi GdMSf Hf LYaQ Hf eMeO Hf GdMSjf s)
(3ChdgG (B:s
(3HGH JSejI Ndb GdEfSGf bGd CNHQfG CHh YHjO GdbGSe Hf SdGe s
(3BNQgG (B:s
(3YRg MaJ GdeQCI hLggG JMaI MakG hNhGakG s
(3HChdg hBNQg SfO GdeUfas
(3hSeGYGJ hbQGAGJs
(3Hg HjGV cKjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B101s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs